Development of a Psychological Well-Being Scale for Adolescents: A Contextual Study of High School Students in Indonesia - Adiba, Nahwa; Setiawati, Farida Agus (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The high level of interest from researchers in the study of psychological well-being necessitates the development of psychological well-being measurement tools in various contexts and cultures, particularly among high school adolescents in Indonesia. This study aims to modify the Indonesian version of the adolescent psychological well-being scale so that it can be used in the context of high school student respondents in Indonesia. The researchers also want to confirm whether the measurement model fits the four-dimensional theory in the context of high school students. This quantitative study involved 420 high school students across all grade levels, residing in South Jakarta, both male and female, and aged around 14-19 years. This study examines three studies: content validity testing by expert judgment using the Gregory format, construct validity testing using the second-order Confirmatory Factor Analysis (CFA) technique, and composite reliability testing using the stratified alpha formula. After going through the modification and adjustment stages, the developed measurement tool can obtain fit and reliable results on 18 items with four dimensions. This can be proven by obtaining a model that meets the fit parameter criteria (CFI = 0.952; TLI = 0.943; SRMR = 0.0516; RMSEA = 0.0451; χ²/df index = 1.8), high Gregory content validity coefficient, and a composite reliability coefficient value of 0.844.Besarnya antusias peneliti terhadap kajian tentang kesejahteraan psikologis memerlukan banyak pengembangan alat ukur kesejahteraan psikologis di berbagai konteks dan budaya, khususnya pada remaja SMA di Indonesia. Penelitian ini bertujuan untuk memodifikasi skala kesejahteraan psikologis remaja versi Indonesia agar dapat digunakan pada konteks responden siswa SMA di Indonesia. Peneliti juga ingin mengonfirmasi model alat ukur tersebut apakah fit dengan teori empat dimensi pada konteks siswa SMA. Penelitian kuantitatif dengan subjek berjumlah 420 siswa SMA di seluruh jenjang kelas, berdomisili di Jakarta Selatan, berjenis kelamin laki-laki maupun perempuan, dan berusia sekitar 14-19 tahun. Penelitian ini mengkaji tiga studi yang meliputi uji validitas isi oleh expert judgement dengan format Gregory, uji validitas konstruk dengan teknik second order Confirmatory Factor Analysis (CFA), dan uji reliabilitas komposit dengan formula alpha berstrata. Setelah melalui tahap modifikasi dan penyesuaian, alat ukur yang dibangun dapat memeroleh hasil yang fit dan reliabel pada 18 butir aitem dengan empat dimensi. Hal tersebut dapat dibuktikan dengan perolehan model yang sesuai dengan kriteria parameter fit (CFI = 0.952; TLI = 0.943; SRMR = 0.0516; RMSEA = 0.0451; indeks χ²/df = 1.8), koefisien validitas isi Gregory yang tinggi, dan nilai koefisien reliabilitas komposit sebesar 0.844.